The political and administrative governance model of the Western Turkic Khaganate in Tokharistan (Academicia Review-A Multidisciplinary Online Journal, 2026)
This study analyzes the nature of the administrative system and vassal relations of the Western Turkic Khaganate over Tokharistan and the adjacent oasis states. Particular attention is paid to the political, military, and administrative mechanisms employed by the Khaganate in governing local rulers, as well as to the control mechanisms of the central authority through the hierarchy of Turkic titles such as eltabar, tudun, tarqan, erkin, shad, and tegin. Based on Chinese, Arabic, Sogdian, and Bactrian sources, the study examines the relationship between Tokharistan and the earlier Hephthalite state, the continuity of local dynasties, and the appointment of representatives of the Turkic elite. It also analyzes the relative autonomy of oasis polities, the taxation system (supervision through tuduns), and the forms of direct and indirect governance. The findings suggest that the governance of the Western Turkic Khaganate was not a single rigidly centralized system but rather a flexible political model that evolved over different stages, in which local dynasties and the Turkic militaryadministrative elite operated jointly.
Keywords: Turkic Khaganate; Tokharistan; eltabar